Fenologia reprodutiva e germinação de sementes de Physalis angulata L., Solanum americanum Mill. e Solanum viarum Dunal - Silva, José Luiz da (2014)
The research was conducted to characterize the reproductive fenology of Physalis angulata, Solanum americanum and S. viarum and the germinative potential of seeds considering the exposition time, light quality and seed storage time. The phenology studies were performed in plants grown in pots and the stages were described according to the observed changes. The fruits biometry data and the seeds production capacity were obtained from fruits collected in the field. Two light experiments were performed: the first was composed by the factorial design 2x10+2, being two light sources (full sun and white fluorescent light), 10 light exposition times (30, 60, 90, 120, 150, 180, 210, 270, 300 minutes) and two controls maintained in the laboratory for comparison (one in the dark and other submited to 10 hours of cold white light); the second was composed by the factorial design 3x5, being three seeds conditions (newly collected, after 40 and 80 days) and five light filter (aluminium foil, transparent film, yellow cellophane paper, red cellophane paper and blue + red cellophane paper). The storage studies were performed by the factorial design 2x9, being two seeds storage conditions (inside the fruits and stored in permeable paper bags) and nine storage periods (30, 60, 90, 120, 150, 180, 210, 240 e 270 days). The reproductive phenology varied in the time for the three species. P. angulata plants entered into reproductive stage at 57.7 ± 2.0 days after emergence (DAE), S. americanum started at 38.3 ± 0.8 DAE and S. viarum at 70.0 ± 0.5 DAE, while the maturation occurred at 100, 73 and 106 DAE, respectively. There was a positive correlation over than 0.68 between fruit mass and number of seeds for S. americanum and S. viarum. The productive capacity of seeds was averaged 259.79 units for P. angulata, 55.01 for S. americanum and 281.54 for S. viarum. The only exposition to direct sunlight or laboratory light was not enough to stimulate seed germination in the established period, different from the observed in the plots exposed to the daily photoperiod of 10 hours, where germination was 56, 58 and 32% for P. angulata, S. americanum and S. viarum respectively. Seeds of P. angulata and S. americanum presented positive photoblastism, with higher germination when exposed to yellow and red light, whereas S. viarum presented neutral photoblastism. Relative to the storage, P. angulata seeds had average germination of 85% and 98%, when stored inside fruits and in paper bags, followed by S. viarum, with 58% and 79% respectively. Seeds extracted from S. viarum remain viable for longer when compared with the two other species.